Critically Strategic HRD: Possibility or Pipe Dream? - Claire Kostopulos Nackoney; Tonette S. Rocco (Adult Education Research Conference, 2008)
This paper examines the strategic and critical paradigms of HRD theoretically, philosophically, conceptually, and practically. Recommendations for integrating the two paradigms are provided.
Keywords: critical theory; critical HRD; strategic HRD; critical management studies